Implementation of the Single Minute Exchange of Dies Method for Reducing Changeover Time in a Hygiene Production Company - Malindzakova, Marcela; Malindzak, Dusan; Garaj, Patrik (International Journal of Industrial Engineering and Management, 2021)
This article focuses on implementing the Single Minute Exchange of Dies (SMED) method within the case study company, a local subsidy of a global producer of hygiene products. Such research was not yet done in the area of Eastern Slovakia, nor was it done for the area of hygiene produce production. The article lists unique specifics taken during the process. The results exceeded the preliminary management expectation, where a changeover time reduction by 30% was achieved. From the managerial perspective, this demonstrates that the SMED method is a mandatory approach for companies struggling with frequent and long changeover times. Article history: Received (February 21, 2021); Revised (July 19, 2021); Accepted (August 2, 2021); Published online (October 28, 2021)